"Mixed" Drinking Motivations: A Comparison of Majority, Multiracial, and Minority College Students. Issue 5 (July 2020) - Straka, Brenda C.; Gaither, Sarah E.; Acheson, Shawn K.; Swartzwelder, H. S.
Social exclusion is associated with substance use, but the specific link between majority and minority racial group membership and substance use is unknown. We examined how social exclusion among racial majority (White), Multiracial, and racial minority (Native American, Latino, Asian, and Black) college students relates to self-reported alcohol use and motivations. Using the AlcoholEdu for College™ survey, Study 1a reports five factors related to motives for initiating or inhibiting alcohol use. Study 1b analyzes majority, Multiracial, and minority college students' comparative endorsement of these motivations. Study 2 compares these factors with established belonging scales using a separate undergraduate sample. White, Multiracial, Native American, and Latino students displayed the highest proportion of problematic alcohol use. White students endorsed belonging-based drinking motivations, while Multiracial and Asian students endorsed motivations similar to both majority and minority groups. Native American, Latino, and Black students endorsed abstaining motivations more than other groups.